2009
DOI: 10.1213/ane.0b013e31818f603c
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Within 2 Years After Surgery in Relation to Low Intraoperative Bispectral Index Values and Preexisting Malignant Disease

Abstract: Using a similar set of co-variates as in previous work, we confirmed the statistical relation between 1-yr mortality and T(BIS <45), and we extended this observation to 2-yr mortality. However, this relation is sensitive to the selection of co-variates in the statistical model, and a randomized study is required to demonstrate that there really is a causal impact from and T(BIS <45) on postoperative mortality and, if it does, the effect is probably very weak in comparison with co-morbidity as assessed by ASA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
2
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(105 citation statements)
references
References 3 publications
4
92
2
7
Order By: Relevance
“…Low intraoperative Bispectral Index (BIS) values have been associated with increased mortality in several studies, [1][2][3][4] although this finding has not been confirmed universally. 5 Because few randomized trials of BIS-targeted anesthesia have been reported, it is unclear whether low BIS values are simply a marker of poor prognosis, or whether targeting anesthetic management based on BIS monitoring could reduce mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Low intraoperative Bispectral Index (BIS) values have been associated with increased mortality in several studies, [1][2][3][4] although this finding has not been confirmed universally. 5 Because few randomized trials of BIS-targeted anesthesia have been reported, it is unclear whether low BIS values are simply a marker of poor prognosis, or whether targeting anesthetic management based on BIS monitoring could reduce mortality.…”
Section: Introductionmentioning
confidence: 99%
“…9 Thus, relatively deep general anesthesia is the norm in routine clinical practice. [10][11][12] Nevertheless, recent research suggests an association between deep general anesthesia and poorer outcomes in surgical patients. 4,5,11,[13][14][15][16][17][18][19][20][21] The dilemma is whether this evidence is strong enough for clinicians to change their practice.…”
Section: Résumémentioning
confidence: 99%
“…If anesthesia is achieved using high doses of hypnotic agents and low doses of anti-nociceptive agents, one may expect that EEG-guided titration will be less efficient at limiting hypnotic agent consumption than in situations with tightly controlled anti-nociception. 57 Controlling for overdosage may prove important, since an association has been found between prolonged time with low EEG indices during anesthesia, and long-term outcome, [58][59][60][61] but not with absolute amount of anesthetic agent received. However, this may reflect an intrinsic sensitivity of the brain to the effect of anesthetic agents in vulnerable patients.…”
Section: Other Clinical Utilitiesmentioning
confidence: 99%